Pengaruh kepribadian neuroticism dan extraversion terhadap fear of missing out pada remaja - Ramadhani, Rivaldi Izza; Suryaningrum, Cahyaning (Cognicia, 2023)
Teenagers is individuals who are vulnerable to experiencing FoMO or fear of missing out. FoMO is a person’s concern about missing moment or activity with the people closest to them. Neuroticism and extraversion is the personality dimensions of the big five personality that can influence adolescents in experiencing FoMO. The purpose this study was to determine the effect neuroticism and extraversion personality on FoMO in adolescents and see which influence is greater between neuroticism and extraversion personality. Instruments used FoMO Scale and BFI. The results of the analysis using multiple linear regression show the probability (p=0.00) indicates that neuroticism and extraversion personality have an influence on FoMO in adolescents. The probability on the neuroticism variable (p=0.00) with a standardized value (β=0.41), while on the extraversion variable (p=0.04) with standardized value (β=0.17), the neuroticism variable has greater influence on the fear of missing out in adolescents than the extraversion variable.Keywords: Adolescent, extraversion, fear of missing out, neuroticism